Pengaruh Karakteristik Pemerintah Daerah Dan Temuan Audit BPK Terhadap Kinerja Penyelenggaraan Pemerintahan Daerah (Studi pada Pemerintah Kabupaten di Sulawesi Selatan Tahun 2009 – 2012) - Peni Sedyaningsih; Achmad Zaky (Jurnal Ilmiah Mahasiswa FEB, 2014)
This research aims to examine the influence of the characteristic of local government (size, level of wealth, dependence level, and government expenditure) and BPK audit finding to the performance of local government. Local government performance is measured by scores on the evaluation of local government performance (EKPPD). Population of this research is all the regencies in South Sulawesi from the year of 2009-2012. Total sample are 80 regencies using purposive random sampling. The result of this research indicates that dependence level and audit findings significant negative influence on the performance of local government. While size, level of wealth, and government expenditure had no influence to the performance of local government in South Sulawesi.Keywords: characteristic of local government, audit finding, the performance of local government, local government organizers report (LPPD), evaluation oflocal government performance (EKPPD)